تمييز الحروف العبرية باستخدام الشبكات العصبية الاصطناعية - د. جمال صلاح الدين سيد مجيد; طارق حازم طه; أسامة ياسين محمد (PROSPECTIVE RESEARCHES, 2023)
In this research, an intelligent computer system has been designed for recognizing printed Hebrew letters by extracting features of the letter by finding the Eigen values which have been used then for training and testing the artificial neural network used in this work namely, Elman NN. This network is used as a tool for decision making. Data were entered using a flatbed scanner which results high extensity, fineness and homogeneous BMP extension images. The programs were implemented by Matlab language, the software include image enhancement techniques, image segmentation, resize the segmented image and features extraction dependent on eigen values and document the final result by visual basic.net because Matlab doesn't have the ability to print the Hebrew letter as a final result.